Racial Feelings : Asian America in a Capitalist Culture of Emotion - Santa Ana, Jeffrey, 1965- (Book collections on Project MUSE., 2015)
"In Racial Feelings, Jeffrey Santa Ana examines how Asian American narratives communicate and critique-to varying degrees-the emotions that power the perception of Asians as racially different. Santa Ana explores various forms of Asian American cultural production, ranging from literature and graphic narratives to film and advertising, to illuminate the connections between global economic relations and the emotions that shape aspirations for the good life. He illustrates his argument with examples including the destitute Filipino immigrant William Paulinha, in Han Ong's Fixer Chao, who targets his anger on the capitalist forces of objectification that racially exploit him, and Nan and Pingpin in Ha Jin's A Free Life, who seek happiness and belonging in America. Racial Feelings addresses how Asian Americans both resist and rely on stereotypes in their writing and art work. In addition, Santa Ana investigates how capitalism shapes and structures an emotional discourse that represents Asians as both economic exemplars and threats."--